The impact of Yohimbine-induced arousal on facets of behavioural impulsivity - Herman, Aleksandra M. (Psychopharmacology (Berl), 2019)
RATIONALE: State-dependent changes in physiological arousal may influence impulsive behaviours. OBJECTIVES: To examine the relationship between arousal and impulsivity, we assessed the effects of yohimbine (an α(2)-adrenergic receptor antagonist, which increases physiological arousal via noradrenaline release) on performance on established laboratory-based impulsivity measures in healthy volunteers. METHODS: Forty-three participants received a single dose of either yohimbine hydrochloride or placebo before completing a battery of impulsivity measures. Blood pressure and heart rate were monitored throughout the study. RESULTS: Participants in the yohimbine group showed higher blood pressure and better response inhibition in the Stop Signal Task, relative to the placebo group. Additionally, individual changes in blood pressure were associated with performance on Delay Discounting and Information Sampling tasks: raised blood pressure following drug ingestion was associated with more far-sighted decisions in the Delay Discounting Task (lower temporal impulsivity) yet reduced information gathering in the Information Sampling Task (increased reflection impulsivity). CONCLUSIONS: These results support the notion that impulsive behaviour is dependent upon state physiological arousal; however, distinct facets of impulsivity are differentially affected by physiological changes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00213-018-5160-9) contains supplementary material, which is available to authorized users.